AN IMPLEMENTATION OF FOUR RESOURCES MODEL OF CRITICAL LITERACY AND NARRATIVE-CULTURAL ANALYSIS IN FILM-BASED ACTIVITY - Solihah, Milda Yulia (2016)
This paper, entitled "An Implementation of Four Resources Model of Critical Literacy and Narrative-Cultural Analysis in Film-Based Activity" aims to investigate the implementation of film-based activity using critical frameworks. A film-based activity consisting of three stages: pre-viewing, while-viewing and post-viewing is developed based on Luke and Freebody's Four Resources Model of critical literacy proposed and Bautista's Narrative-Cultural Approach in order to achieve the purpose of this study. The activity is performed to 48 ninth-grade students by the researcher who also serves as the teacher in this practitioner research. Students are guided to write three individual responses and participate in group discussion. Some of their responses are also confirmed in focus groups interview. As a result, students show capability to become critical readers, playing the role as code breaker, meaning maker, text user and text analyst as the realization of the four resources model: breaking the code, participating in making meaning of the text, using the text functionally and critically analyzing the text. Key words: film-based activity, critical frameworks, critical literacy, four resources model, narrative-cultural analysis Skripsi yang berjudul "Implementasi Model Empat Elemen Literasi Kritikal dan Analisis Naratif-Kultural dalam Pembelajaran Berbasis Film" ini bertujuan untuk menginvestigasi penerapan aktivitas pembelajaran berbasis film dengan menggunakan kerangka kritikal. Guna mencapai tujuan penelitian, aktivitas pembelajaran berbasis film yang terdiri dari tiga tingkatan: pre-pengamatan, pengamatan dan pos-pengamatan dikembangkan berdasarkan teori Empat Elemen Literasi Kritikal dari Luke dan Freebody serta Pendekatan Naratif-Kultural dari Bautista. Pembelajaran tersebut diberikan kepada 48 siswa kelas 9 oleh peneliti yang juga bertindak sebagai guru/instruktur dalam penelitian ini. Siswa dibimbing untuk menulis tiga respon individual dan berpartisipasi dalam diskusi kelompok. Beberapa respon mereka juga dikonfirmasi dalam wawancara kelompok. Hasilnya, siswa menunjukkan kemampuan untuk menjadi pembaca kritis dengan berperan sebagai pemecah kode, pembuat makna, pengguna teks dan analis teks, yakni realisasi dari keempat elemen literasi: memecahkan kode, berpartisipasi dalam memaknai teks, menggunakan teks secara fungsional dan menganalisis teks secara kritis. Kata kunci: pembelajaran berbasis film, kerangka kritikal, literasi kritikal, model empat elemen literasi kritikal, analisis naratif-kultural